Clinical features, laboratory characteristics, and outcome of ETP and TCRA/D aberrations in pediatric patients with T-acute lymphoblastic leukemia - Mona S. El Ashry; Enas Radwan; Mona S. Abdellateif; Omar Arafah; Naglaa M. Hassan (Journal of the Egyptian National Cancer Institute, 2023)
Abstract Background T-cell acute lymphoblastic leukemia (T-ALL) is an aggressive malignancy with few accepted prognostic factors that limit the efficiency of therapy. The aim of the current study was to assess the clinical and laboratory features of T-cell receptor (TCR) aberrations and early T-cell precursor (ETP) subtype as well as their outcome to therapy. Methods Sixty-three newly diagnosed pediatric T-ALL patients were assessed for the ETP status using immunophenotyping. Screening of TCRA/D aberrations was done by fluorescent in situ hybridization (FISH). The data were correlated to the patients’ clinical features, response to treatment, and survival rates. Results Seven patients (11%) had ETP-ALL. The ETP-ALL patients were older (P = 0.013), presented with lower white blood cell (WBC) count (P = 0.001) and lower percentage of peripheral blood (PB) blast cells (P = 0.037), more likely to have hyperdiploid karyotype (P = 0.009), and had been associated with TCRA/D gene amplification (P = 0.014) compared to other T-ALL patients. Of note, the same associations had been significantly observed in patients with TCRA/D gene amplification. Patients with TCRA/D amplification frequently coincided with TCRβ aberrations (P = 0.025). TCR-β aberrations were significantly associated with negative MRD at the end of induction compared to TCR-β-negative patients. There was a nonsignificant trend of ETP-positive cases to have lower overall survival (OS) (P = 0.06). Patients with TCR aberrations had no significant differences regarding disease-free survival (DFS) or OS rates compared to those with normal TCR. Conclusion ETP-ALL patients tend to have increased mortalities. There was no significant impact of TCR aberrations on the survival rates of the patients.